The Role of Micro, Small, Medium Enterprises in Enhancing Post-Covid Community-Based Tourism - Fitria Noviati; Kiki Rizki Makiya; Meiana Maulida Hikmawati (Universitas Mataram, 2022)
Approaching a three-year mark since the onset of Covid-19 pandemic, tourism remains in the forefront of Indonesia’s overall recovery strategy, along with the micro, small and medium-sized enterprises (MSMEs) that have also been the backbone of the country’s economy. The field of community-based tourism (CBT), which has developed around the growth of these MSMEs, has increasingly gained traction in the Indonesian tourism research community in the past decade or so. However, there remains a great deal to be explored, particularly in relation to attaining sustainability in the face of global crisis such as the Covid-19 pandemic. This study aims to analyze the role of MSMEs in enhancing CBT, focusing on their business strategies prior to and following the onset of the pandemic. A descriptive qualitative method is utilized by means of content analysis and literature review, both from primary and secondary sources. The resulting analysis reveals that the role of MSMEs significantly contribute to enhance community-based tourism strategy before and after the pandemic. The study also reveals that following the Covid-19 pandemic, MSMEs’ business and development strategies shifted toward increasing and improving utilization of digital technology and literacy across all MSME sectors.